2005
DOI: 10.1016/j.jhealeco.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Classic or new monopsony? Searching for evidence in nursing labor markets

Abstract: The market for registered nurses (RNs) is often offered as an example of "classic" monopsony, while a "new" monopsony literature emphasizes that firm labor supply is upward sloping independent of market structure. Using data from multiple sources, we explore the relationship between nursing wages in hospitals and measures of classic and new monopsony. Wage level analysis fails to provide support for classic monopsony, the relative wages of RNs in 240 U.S. labor markets being largely uncorrelated with hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…Including previous tenure controls further reduces the size of the coe¢ cients but not very much. 17 Then, I use the wage elasticity of separations to employment " e sw to recover the wage elasticity of recruits from employment " e Rw . The separation elasticity to non employment " n sw is estimated on the sample of changers for those that don't get a new job when moving.…”
Section: Wage Elasticities Of Separations and Estimates From A Dynamimentioning
confidence: 99%
See 2 more Smart Citations
“…Including previous tenure controls further reduces the size of the coe¢ cients but not very much. 17 Then, I use the wage elasticity of separations to employment " e sw to recover the wage elasticity of recruits from employment " e Rw . The separation elasticity to non employment " n sw is estimated on the sample of changers for those that don't get a new job when moving.…”
Section: Wage Elasticities Of Separations and Estimates From A Dynamimentioning
confidence: 99%
“…This again suggests that the monopsony model in its dynamic (oligopsonistic) version can help to explain the wage gender di¤erential. 17 Here I don't consider any endogeneity issue for tenure. 20 …”
Section: Wage Elasticities Of Separations and Estimates From A Dynamimentioning
confidence: 99%
See 1 more Smart Citation
“…Their analyses conclude that the labor market for registered nurses is not a monopsony because nurses have considerable mobility between hospitals. Hirsch and Schumacher (2005) also indicate that when many new individuals enter a market, the market might have high mobility for workers, demonstrating a lower level of monopsony. It is also suggested that if the entry of employees comes from the unemployed (including inactive individuals considered in our framework), it would lead to weaker mobility for nurses between hospitals.…”
Section: Critique Of Heyes' Modelmentioning
confidence: 98%
“…Although this does not necessarily mean we fully accept Heyes' model, vocation is a significant factor in our framework, as we focus on inactive nurses who have already obtained an assured level of skill and knowledge in this field and are temporarily out of work because of birth and childcare as opposed to newcomers without vocation. Hirsch and Schumacher (2005) explain that the market for registered nurses in the United States is an example of a monopsonistic labor market, where the larger the degree of monopsony, the lower the wage rate becomes. If monopsonistic power were stronger in this market, the wage rate would be lower than that of a competitive case, as pointed out by Hurd (1973) and Taylor (2007), meaning that nursing shortages would persist.…”
Section: Critique Of Heyes' Modelmentioning
confidence: 99%